2-Bromo-4-chloro-6-[(2,6-diisopropylphenyl)iminomethyl]phenol - Raja, K. Kanmani (International Union of Crystallography, 2008)
There are two molecules in the asymmetric unit of the title compound, C(19)H(21)BrClNO, with dihedral angles between the aromatic rings of 70.0 (2) and 81.9 (3)°. The crystal structure is stabilized by intermolecular C—H⋯π and C—Br⋯π interactions. In additional, the stacked molecules exhibit intramolecular O—H⋯N hydrogen bonds.